Cytoskeletal function in CD8- and T cell receptor-mediated interaction of cytotoxic T lymphocytes with class I protein (The Rockefeller University Press, 1991)
Cloned allospecific cytolytic T lymphocytes (CTL) adhere to purified class I alloantigen immobilized on plastic and degranulate in response to it. Binding and degranulation are inhibited by drugs that impair cytoskeletal function. Cytochalasins D and E, which interfere with microfilament function, and colchicine, which disrupts microtubules, were used and gave qualitatively similar results. Concentrations of these drugs that inhibited degranulation in response to alloantigen did not inhibit response to immobilized anti-T cell receptor (TCR) antibody. Neither did they inhibit response when alloantigen was co- immobilized with an antibody against class I on the CTL to promote adhesion between the CTL and antigen-bearing surface. Thus, neither transmembrane signal generation via the TCR nor degranulation per se were prevented. Instead, the drugs act to prevent the initial adhesion to alloantigen. CTL binding to alloantigen depends in part on CD8-class I interaction, and adhesion via CD8 is "activated" by crosslinking the TCR with soluble anti-TCR antibody. This adhesion, too, is shown to be cytoskeleton dependent.